2018
DOI: 10.1111/nph.15215
|View full text |Cite
|
Sign up to set email alerts
|

Testing the roles of vertical transmission and drought stress in the prevalence of heritable fungal endophytes in annual grass populations

Abstract: Beneficial inherited symbionts are expected to reach high prevalence in host populations, yet many are observed at intermediate prevalence. Theory predicts that a balance of fitness benefits and efficiency of vertical transmission may interact to stabilize intermediate prevalence. We established populations of grass hosts (Lolium multiflorum) that varied in prevalence of a heritable fungal endophyte (Epichloё occultans), allowing us to infer long-term equilibria by tracking change in prevalence over one genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The results from this study are relevant for understanding the ecological dynamics of the plant-endophyte symbiosis in natural and managed ecosystems. Vertical transmission efficiency, which also involves endophyte persistence in seed, is an important process controlling the incidence of Epichloë fungal endophytes in grass populations (Afkhami & Rudgers, 2008;Cavazos et al, 2018;Gundel, Garibaldi, et al, 2011;Gundel, Rudgers, et al, 2011). In addition, this study showed that there was an alignment of the partners' fitness; the higher the seed production, the higher multiplication rate of the fungus and higher concentration of alkaloids in seed.…”
Section: Discussionmentioning
confidence: 76%
“…The results from this study are relevant for understanding the ecological dynamics of the plant-endophyte symbiosis in natural and managed ecosystems. Vertical transmission efficiency, which also involves endophyte persistence in seed, is an important process controlling the incidence of Epichloë fungal endophytes in grass populations (Afkhami & Rudgers, 2008;Cavazos et al, 2018;Gundel, Garibaldi, et al, 2011;Gundel, Rudgers, et al, 2011). In addition, this study showed that there was an alignment of the partners' fitness; the higher the seed production, the higher multiplication rate of the fungus and higher concentration of alkaloids in seed.…”
Section: Discussionmentioning
confidence: 76%
“…Future research will have to investigate the maternal and environmental drivers of the rate of vertical transmission of microorganisms (e.g. Cavazos et al , 2018; Sneck et al , 2017; Leff et al , 2017), and assess the role of these microorganisms on seed survival and germination, seedling growth and health (e.g. Vivas et al , 2017; Leroy et al , 2019), and ultimately tree fitness.…”
Section: Resultsmentioning
confidence: 99%
“…Symbionts can allow their hosts to cope with global change (Kivlin et al, 2013;Cavazos et al, 2018), yet our work suggests that associations with the Epichloë endophyte can be gradually lost over time with reduced precipitation. These findings could suggest that A. breviligulata's association with Epichloë may be particularly costly under drought conditions or that Epichloë itself may be unable to persist in drought-exposed host plants.…”
Section: Symbiont Loss Under Global Changementioning
confidence: 90%
“…non-epichloid taxa to colonize (Zimmerman and Vitousek, 2012;Giauque and Hawkes, 2013), but will not directly affect the arrival and establishment of vertically transmitted Epichloë (Rodriguez et al, 2009). Maintaining symbiosis with Epichloë will typically depend on the costs and benefits of symbiosis in the novel environmental context and the rate of vertical transmission (Cheplick, 2007;Davitt et al, 2010;Emery et al, 2010;Gundel et al, 2011;Yule et al, 2013;Cavazos et al, 2018).…”
mentioning
confidence: 99%